Anti-stress effects of ginseng via down-regulation of tyrosine hydroxylase (TH) and dopamine β-hydroxylase (DBH) gene expression in immobilization-stressed rats and PC12 cells - Kim, Y.H., Ewha Womans University, Seoul, Republic of Korea; Choi, E.H., Ewha Womans University, Seoul, Republic of Korea; Doo, M.A., Ewha Womans University, Seoul, Republic of Korea; Kim, J.Y., Ewha Womans University, Seoul, Republic of Korea; Kim, C.J., Korea Food Research Institute, Sungnam, Republic of Korea; Kim, C.T., Korea Food Research Institute, Sungnam, Republic of Korea; Kim, I.H., Korea University, Seoul, Republic of Korea (Nutrition research and practice, 2010)
Catecholamines are among the first molecules that displayed a kind of response to prolonged or repeated stress. It is well established that long-term stress leads to the induction of catecholamine biosynthetic enzymes such as tyrosine hydroxylase (TH) and dopamine β-hydroxylase (DBH) in adrenal medulla. The aim of the present study was to evaluate the effects of ginseng on TH and DBH mRNA expression. Repeated (2 h daily, 14 days) immobilization stress resulted in a significant increase of TH and DBH mRNA levels in rat adrenal medulla. However, ginseng treatment reversed the stress-induced increase of TH and DBH mRNA expression in the immobilization-stressed rats. Nicotine as a ligand of the nicotinic acetylcholine receptor (nAChR) in adrenal medulla stimulates catecholamine secretion and activates TH and DBH gene expression. Nicotine treatment increased mRNA levels of TH and DBH by 3.3- and 3.1-fold in PC12 cells. The ginseng total saponin exhibited a significant reversal in the nicotine-induced increase of TH and DBH mRNA expression, decreasing the mRNA levels of TH and DBH by 57.2% and 48.9%, respectively in PC12 cells. In conclusion, immobilization stress induced catecholamine biosynthetic enzymes gene expression, while ginseng appeared to restore homeostasis via suppression of TH and DBH gene expression. In part, the regulatory activity in the TH and DBH gene expression of ginseng may account for the anti-stress action produced by ginseng.